A Novel Catalytic Function of Synthetic IgG‐Binding Domain (Z Domain) from Staphylococcal Protein A: Light Emission with Coelenterazine. (27th November 2013) - Inouye, Satoshi; Sahara‐Miura, Yuiko
Abstract The synthetic IgG‐binding domain (Z domain) of staphylococcal protein A catalyzes the oxidation of coelenterazine to emit light like a coelenterazine‐utilizing luciferase. The Z domain derivatives (ZZ‐gCys, Z‐gCys and Z‐domain) were purified and the luminescence properties were characterized by comparing with coelenterazine‐utilizing luciferases, including Renilla luciferase, Gaussia luciferase and the catalytic 19 kDa protein of Oplophorus luciferase. Three Z domain derivatives showed luminescence activity with coelenterazine and the order of the initial maximum intensity of luminescence was ZZ‐gCys (100%) > Z‐gCys (36.8%) > Z‐domain (1.1%) > bovine serum albumin (BSA; 0.9%) > staphylococcal protein A (0.1%) and the background value of coelenterazine (0.1%) in our conditions. The luminescence properties of ZZ‐gCys showed the similarity to that of Gaussia luciferase, including the luminescence pattern, the emission spectrum, the stimulation by halogen ions and nonionic detergents and the substrate specificity for coelenterazine analogues. In contrast, the luminescence properties of Z‐gCys were close to the catalytic 19 kDa protein of Oplophorus luciferase. The catalytic region of the Z domain for the luminescence reaction might be different from the IgG‐binding region of the Z domain.